Narrative Coherence of Turning Point Memories: Associations With Psychological Well-Being, Identity Functioning, and Personality Disorder Symptoms - Vanderveren, Elien; Bogaerts, Annabel; Claes, Laurence; Luyckx, Koen; Hermans, Dirk (Frontiers in Psychology, 2021)
Individuals develop a narrative identity through constructing and internalizing an evolving life story composed of significant autobiographical memories. The ability to narrate these memories in a coherent manner has been related to well-being, identity functioning, and personality pathology. Previous studies have particularly focused on coherence of life story narratives, overlooking coherence of single event memories that make up the life story. The present study addressed this gap by examining associations between narrative coherence of single turning point memories and psychological well-being, identity functioning, and personality disorder (PD) symptoms among 333 Belgian emerging adults (72.1% female; Mage = 22.56, SD = 3.13, age range = 18-30). In addition, the present study tested whether narrative coherence could predict unique variance in PD symptoms above and beyond identity and interpersonal functioning, both considered key components of personality pathology. The findings showed that narrative coherence was not significantly related to psychological well-being, but yielded significant negative associations with disturbed identity functioning and antisocial PD symptoms. Furthermore, narrative coherence predicted unique variance in antisocial PD symptoms above and beyond identity functioning, but did not predict unique variance in borderline and antisocial PD symptoms above and beyond both identity and interpersonal functioning. Collectively, these findings suggest that narrative incoherence within single event memories might be characteristic for disturbed identity functioning and antisocial personality pathology.